Flavonoids improve type 2 diabetes mellitus and its complications: a review - Yi, Xinrui; Dong, Mosi; Guo, Naifei; Tian, Jinlong; Lei, Ping; Wang, Song; Yang, Yufeng; Shi, Yan (Frontiers in Nutrition, 2023)
The prevalence of type 2 diabetes mellitus (T2DM) is increasing every year. Medications are currently the most common therapy for T2DM. However, these medications have certain adverse effects. In order to find safe and effective ways to improve this disease, researchers have discovered that some natural products can decrease blood sugar. Flavonoids are one of the most essential low molecular weight phenolic chemicals in the plant world, which widely exist in plant roots, stems, leaves, flowers, and fruits. They possess a variety of biological activities, including organ protection, hypoglycemic, lipid-lowering, anti-oxidative and anti-inflammatory effects. Some natural flavonoids ameliorate T2DM and its complications through anti-oxidation, anti-inflammatory action, glucose and lipid metabolism regulation, insulin resistance management, etc. Hence, this review aims at demonstrating the potential benefits of flavonoids in T2DM and its complications. This laid the foundation for the development of novel hypoglycemic medications from flavonoids.